Analyses of registry data of patients with anti-GBM and antineutrophil cytoplasmatic antibody-associated (ANCA) vasculitis treated with or without therapeutic apheresis. (December 2021) - Mörtzell Henriksson, M.; Weiner, M.; Sperker, W.; Berlin, G.; Segelmark, M.; Javier Martinez, A.; Audzijoniene, J.; Griskevicius, A.; Newman, E.; Blaha, M.; Vrielink, H.; Witt, V.; et al.
Abstract: Therapeutic apheresis (TA) as a treatment for antibody-associated vasculitis (AAV) was questioned by the PEXIVAS although the MEPEX study favored TA. The aim of this study was to evaluate the efficacy of TA to improve renal function in patients consecutively included in the WAA-apheresis registry versus patients not treated with TA. Materials and methods: Included were 192 patients that suffered from anti-glomerular basement membrane disease (anti-GBM, n = 28) and antineutrophil cytoplasmic antibody-associated vasculitis of MPO or PR3 origin. Of these 119 had performed TA and the other 73 had not performed TA for theses diagnoses (CTRL). Results: Elderly had an increased risk to die within 12 months (p = 0.002). All 28 anti-GBM had renal involvement, 21 dialysis dependent. At 3 month nine (36 %) did not need dialysis. Baseline data regarding renal function of AAV patients, subtype MPO and PR3, were worse in the TA groups than in CTRL. Recovery out of dialysis was better for the PR3-TA group compared with 1) the controls of MEPEX (RR 0.59, CI 0.43−0.80) and 2) the MPO-TA patients (RR 0.28, CI 0.12−0.68). The MPO-TA recovered similarly as the MEPEX-CTRL. Renal function improved most for TA-patients from baseline during the first 3 months (MPO-TA and PR3-TA) and stabilized thereafter and less for MPO-CTRL and PR3-CTRL. Conclusion: PR3-TA patients seem to have best chances to get out of dialysis. PR3-TA and MPO-TA improved residual renal function better than CTRL. The present study recommends reconsiderations to use TA for AAV especially those with PR3-vasculitis with severe renal vasculitis.